Exploring the link between change- and knowledge management: How to identify employees that utilize their tacit knowledge to sabotage organizational change initiatives. - Jung, Hans Philip (2010)
The theories in the fields of change and knowledge management are established. Recently individual links between the two areas have been explored and tested, yet the theories remain discrete. Numerous models for change initiative implementation exist but are insufficient in explaining causes of resistance and inertia. This paper explores the relationships between change and knowledge management and seeks to integrate the relationships. Exploration of how employees utilize their tacit knowledge to resist and sabotage change is conducted by a case study approach. The qualitative analysis of four data sources (internal and external) allows for triangulation to increase findings’ validity. It is concluded that change management and in particularly change initiatives demonstrate a strong link to knowledge management. The fields are linked in the eight strongest factors im-pacting change initiative success. Individuals’ knowledge and how it is affected by a change initiative determines their likelihood of resistance to the change. Senior management and change agents ought to be aware of the impact knowledge and capability have on change ini-tiative success.